Obtenção de LiFePO4 via síntese assistida por microondas, caracterização e testes eletroquímicos visando sua aplicação como catodos em baterias de íons lítio - Smecellato, Pamela Cristina (Universidade Federal de São Carlos, 2015)
In this work, studies on the optimization of the LiFePO4 synthesis were performed, aiming to obtain a product, at shorter calcination times, with smaller particle size and promising electrochemical properties for applications as cathode material in lithium ion batteries. Crystalline LiFePO4 was synthesized through the combination of carbothermal reduction and microwave-assisted solid-state reaction. The precursors LiOH.H2O, FePO4.4H2O, glucose and graphite were exposed to carbothermal reduction at 200 ºC during 3 h and subsequently calcined by irradiation with microwaves at 800 W for varying times, from 1 to 5 min. The obtained products were analyzed through thermal analysis using TGADTG and DSC curves. Their structural, morphological and electrochemical properties were investigated by means of X-Ray diffractometry, infrared spectroscopy, scanning electron microscopy and cyclic voltammetry, respectively. The product obtained at 3 min, besides presenting the smallest particle size (100 to 150 nm), was the only one with a crystalline phase and a voltammetric profile characteristic of LiFePO4 between 3,2 and 3,7 V vs. Li/Li+ in a solution of 1 mol L-1 LiClO4 in EC/DMC (1:1 V/V). The electrode was prepared with LiFePO4, acetylene black and PVDF (85:10:5 m/m/m), and the diffusion coefficient of Li ions in the LiFePO4 phase was estimated as 0,29.10–14 cm2 s-1. Galvanostatic charge-discharge tests were performed with this electrode between 3,8 and 3,1 V vs. Li/Li+ under the same experimental conditions as in the cyclic voltammetry. The obtained LiFePO4 presented an initial specific capacity of 100 mA h g-1 at C/4, considering 39,8% of active material.
Preparation of lifepo4 via microwave assisted synthesis, characterization and electrochemical tests aiming its application as cathodes in lithium ion batteries
Keywords: LiFePo4; Síntese em estado sólido; Síntese por micro-ondas; Catodos; Baterias de íons lítio; CIENCIAS EXATAS E DA TERRA::QUIMICA